The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4034/pboci.2018.181.18
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Asthma, Malocclusion and Mouth Breathing in Primary Health Care Children

Abstract: Objective: To assess the relationship between asthma, malocclusion and mouth breathing. Material and Methods: This investigation was a cross-sectional study of 228 children between 6 and 12 years of age, of whom 112 were asthmatic and 116 were not, performed in two Primary Health Units of Porto Alegre, Brazil. The assessment consisted of a mouth exam performed by two calibrated dentists, an interview with parents/caregivers and medical chart data. Mouth breathing was determined through oral-facial changes rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The literature review indicates that obstructive factors such as adenotonsillar hypertrophy and deviation of the nasal septum; inflammatory factors such as asthma and allergic rhinitis; functional factors such as the appearance of oral habits are associated with the presence of mouth breathing (Graph 1) [3,[20][21][22][23][24][25][26][27].…”
Section: Analysis and Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review indicates that obstructive factors such as adenotonsillar hypertrophy and deviation of the nasal septum; inflammatory factors such as asthma and allergic rhinitis; functional factors such as the appearance of oral habits are associated with the presence of mouth breathing (Graph 1) [3,[20][21][22][23][24][25][26][27].…”
Section: Analysis and Discussion Of Resultsmentioning
confidence: 99%
“…Asthma is a chronic inflammatory disease of the airways, where wheezing, dyspnea, chest tightness, and cough occur, which can be reversible or secondary symptoms, sometimes causing airway obstruction [23,24].…”
Section: Inflammatory Factorsmentioning
confidence: 99%
“…Regarding the relationship between asthma and the presence of mouth breathing habits, the results of our study indicated that 46.7% of patients with asthma presented this habit, which coincides with the result reported by Lopes dos Santos et al in 2012. Using a chi-squared statistical test, they found an association between asthma and mouth breathing ( p < 0.001), with 66.3% of children with asthma suffering from this harmful habit [ 25 ]. Other authors such as Stensson et al [ 26 ] support Lopes dos Santos.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors such as Stensson et al [ 26 ] support Lopes dos Santos. When comparing a group of healthy children with one of children with asthma, they established that asthmatics presented the habit of oral breathing twice as much as the control group [ 25 , 26 ]. Additionally, in a systematic review and meta-analysis by Araujo et al, 12,147 subjects were examined, including 2083 children.…”
Section: Discussionmentioning
confidence: 99%